2010
DOI: 10.1002/app.31563
|View full text |Cite
|
Sign up to set email alerts
|

Rubber‐like thermosetting epoxy asphalt composites exhibiting atypical yielding behaviors

Abstract: Rubber-like thermosetting epoxy asphalt composites (REACs) were prepared by curing epoxy resin (diglycidyl ether of bisphenol A) with curing agents system made up of maleated petroleum asphalt, adipic acid, and methylhexahydrophthalic anhydride. REACs' glass transition temperatures (T g ) and mechanics performances were investigated by differential scanning calorimetry (DSC) and universal tester, respectively. DSC results indicated that REACs had homogeneous phase structures, and their T g were lower than room… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 39 publications
0
33
1
1
Order By: Relevance
“…In China, EA concrete has been used in more than 40 long‐span bridges since 2000. Furthermore, EA concrete has also been used in tunnels, pavement at intersections of heavy duty roads, and porous asphalt pavements with high durability …”
Section: Introductionmentioning
confidence: 99%
“…In China, EA concrete has been used in more than 40 long‐span bridges since 2000. Furthermore, EA concrete has also been used in tunnels, pavement at intersections of heavy duty roads, and porous asphalt pavements with high durability …”
Section: Introductionmentioning
confidence: 99%
“…2 (a is at 20 °C, and b is at 0 °C). All samples had elastic properties similar to those of anhydride cured thermosetting EACs at 20 °C; as the asphalt content increases, the tensile strength decreases and the rupture elongation is enhanced 16 . Previous studies have demonstrated that the addition of asphalt has no influence on the extent of the epoxy curing reaction under the same curing conditions 25 .…”
Section: Resultsmentioning
confidence: 77%
“…Conventionally, the characterization method of EACs has been borrowed from the characterization of plastics, for example, ASTM D 638–2010: Standard Test Method for the Tensile Properties of Plastics 12 13 16 17 18 19 20 21 25 . To compare the performance of polyetheramine-cured EACs, direct tensile tests were performed with a universal tester at 20 °C and 0 °C, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the epoxy resin-modified asphalt emulsion contains chemical reaction functional groups, such as carboxyl, hydroxyl, epoxy and other organic functional groups, which can coordinate or crosslink with Ca 2þ , Al 3þ of cement hydration products (Ohama, 1998). In addition, chemical modified asphalt emulsion (with an organic amine group) can also react with epoxy resin at room temperature to form a 3D interpenetrating gel network structure (Kang et al, 2010a(Kang et al, , 2010b. Owing to the 'fibre reinforced' effect of this structure, the epoxy asphalt cement mortar has a relatively high compressive strength.…”
Section: Resultsmentioning
confidence: 98%